Intertwining Paths. My Experiences of Collaboration in Artistic Research in Community Making - Dávila López, Angélica Jarumi (2021)
This article addresses the proposal of Artistic Research as the axis of the Research in Visual Arts subject that the author teaches in the Master of Visual Arts of the Postgraduate Degree in Arts and Design at Universidad Nacional Autónoma de México (UNAM), based on the work carried out with the students, the importance of the creative process is revalued and the idea of experience as a collaborative element to form a community is emphasized during the development of the research project. For which, both theoretical and experiential sources are taken up, referring to researchers specializing in the subject, and to the inquiries derived from experiences lived at various moments of the author’s training and professional performance so it is a process deconstructive of what used to be understood and developed as research. Complemented with three images as a logbook.